Prevalence of Depression, Anxiety, and Stress Among Indonesian Healthcare Workers During the Covid-19 Pandemic and Its Related Factors - Tan, Alexa Ovilia; Angelina, Angelina (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
Introduction: Healthcare workers are the most vulnerable group to infection and mental-emotional problems due to their professional exposure during the COVID-19 pandemic. The studies about healthcare workers’ mental-emotional problems in Indonesia are still limited. This study aimed to determine the prevalence of depression, anxiety, and stress among Indonesian healthcare workers during the COVID-19 pandemic and its related factorsMethods: This is an analytic cross-sectional study involving Indonesian healthcare workers who were still working during the COVID-19 pandemic. An online-based questionnaire in Google Form, including the Depression Anxiety and Stress Scale - 21 (DASS-21) Questionnaire, was distributed through social media from December 2020 to February 2021. The related factors studied were age, gender, domicile, worktime experience, workplace, type of workers, marital status, comorbidities, and COVID-19 history. Results: A total of 176 respondents were involved in the study, the overall prevalence of mental-emotional problems was 18.75%; with a prevalence of depression was 10.8%, anxiety 12.5%, and stress 12.5%. The incidence of depression was more commonly found in non-functional occupations (OR 4.97; 95% CI 1.00-24.69; p=0.05). The incidence of anxiety was less common in male health workers (OR 0.23; 95% CI 0.08 - 0.66; p=0.007), and nurse occupation (OR 6.41; 95% CI 1.65 - 24.86, p=0.007). The incidence of stress was more commonly found in nurse (OR 8.38; 95% CI 1.49 - 47.13; p=0.014), non-functional (OR 10.17; 95% CI 1.78 - 58.04; p=0.008).Conclusion: Mental emotional problems during the COVID-19 pandemic were common among Indonesian healthcare workers, both the front-liners and non-functional health workers. Gender and type of worker were significantly associated with depression, anxiety, and stress.